Case study: analysis of the degree of innovation in four companies in the field of information and communication technology – TICS, by the Innovation Radar methodology (Revista Brasileira de Contabilidade e Gestão, 2023)
The article examines the innovation degree of four company of Information and Communication Technology (ICTs) at city of Pelotas / RS. It was used the methodology Innovation Radar, called dimensions of innovation Sawhney et al (2006) and Bachmann and Destefani (2008). ). The results showed that innovation has greater presence in the dimension ambience innovative, with informal atmosphere, little bureaucracy that generated the new ideas. However, presence dimension has the lowest degree of innovation, being ineffective in proposing new forms of distribution of products / services or improve existing points innovatively. it was identified the importance of innovation and planning,it was evidenced various ways to innovate in company.
Keywords: innovation; companies; technology